2019
DOI: 10.1016/j.ijcha.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Networking analysis on superior vena cava arrhythmogenicity in atrial fibrillation

Abstract: Atrial fibrillation (AF) can be initiated from arrhythmogenic foci within the muscular sleeves that extend not only into the pulmonary veins but also into both vena cavae. Patients with SVC-derived AF have the common clinical and genetic risk factors. Bayesian network analysis is a probabilistic model in which a qualitative dependency relationship among random variables is represented by a graph structure and a quantitative relationship between individual variables is expressed by a conditional probability.We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Various studies attempt to analyze the frequencies of single-nucleotide polymorphisms (SNPs) in genes whose protein products are involved in the pathogenesis of AF. Genome-wide association (GWAS) in the Japanese population identified that rs2200733, rs10033464 (located in the PITX2), and rs6584555 (located in the NURL1) were associated with AF [ 94 ]. In previous studies in Japan, six more loci were associated with AF: at 1q24 in PRRX1 (rs593479), 4q25 near PITX2 (rs2634073), 7q31 in CAV1 (rs1177384), 10q25 in NURL1 (rs6584555), 12q24 in CUX2 (rs649002), and 16q22 in ZFHX3 (rs12932445) [ 95 ].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Various studies attempt to analyze the frequencies of single-nucleotide polymorphisms (SNPs) in genes whose protein products are involved in the pathogenesis of AF. Genome-wide association (GWAS) in the Japanese population identified that rs2200733, rs10033464 (located in the PITX2), and rs6584555 (located in the NURL1) were associated with AF [ 94 ]. In previous studies in Japan, six more loci were associated with AF: at 1q24 in PRRX1 (rs593479), 4q25 near PITX2 (rs2634073), 7q31 in CAV1 (rs1177384), 10q25 in NURL1 (rs6584555), 12q24 in CUX2 (rs649002), and 16q22 in ZFHX3 (rs12932445) [ 95 ].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…28 Over the past few years, BNs have been extensively used to model clinical problems in CVD for the purposes of diagnosis, risk assessment and disease prediction. [29][30][31][32][33] In the present study, we introduced a BN analysis to evaulate the aetiological role of HCV infection in CVD risk. Our objective is to characterise the multivariable probabilistic connection between the two diseases and identify factors that mediate and influence this relationship in a population of Canadian adults.…”
Section: Open Accessmentioning
confidence: 99%
“… 16 17 These relationships are represented by a graphical structure, whereas the quantitative dependencies between individual variables are expressed as a conditional probability. 18 Over the last years, BNs have been extensively used to model diagnosis, risk assessment and disease prediction in the context of cardiovascular diseases, 19–21 but have not yet been much explored in the context of T2DM. Recently, a few studies developed promising approaches applying deep learning neural networks and comparative machine-learning approaches for predicting T2DM.…”
Section: Introductionmentioning
confidence: 99%